Challenge Test to Assess the Microbial Inhibitory Potential of Lactic Acid Bacteria in Ice-Kenkey - Amy Atter; Michael Amoo-Gyasi; Richard Yaw Otwey; Felix Afotey; Angela Parry-Hanson Kunadu; Wisdom Amoa-Awua (Journal of Food Quality)
Foods fermented by lactic acid bacteria (LAB) are considered safer and healthier due to LAB’s ability to inhibit pathogen growth and produce bioactive compounds. The study aimed to evaluate the antimicrobial potential of lactic acid bacteria (LAB) in ice-kenkey, a chilled Ghanaian fermented maize beverage, against common foodborne pathogenic bacteria and to determine the duration of inhibition during ambient storage, all in the interest of promoting public health and safety. Samples of ice-kenkey obtained from a small-scale producer and ice-kenkey produced in the laboratory were inoculated with overnight pure cultures of Escherichia coli, Bacillus cereus, Staphylococcus aureus, Vibrio parahaemolyticus, and Salmonella spp. in nutrient broth at concentrations of about 108–109 CFU/ml during storage at room temperature (≈27°C). The population of the different pathogens in both samples of ice-kenkey was enumerated at different storage periods to assess their survival in the ice-kenkey, hence the antimicrobial activity of the ice-kenkey. The pH of both types of ice-kenkey was below 5.0 throughout the storage period of up to 140 h. The commercial ice-kenkey had higher LAB and yeast counts. For both types of ice-kenkey, there was a steady increase in the population of LAB and yeasts from the 0 h to 72 h period, followed by a steady decline from the 96 h to the 120 h period. There were variations in the survival of the different enteric pathogens in the ice-kenkey samples. Vibrio cholera and Salmonella spp. were not detected in both types of ice-kenkey within 8–24 h of storage at room temperature. However, for Escherichia coli, Bacillus cereus, and Staphylococcus aureus, there were no significant reductions in their population within the first 8 h of the storage of both the laboratory and commercial ice-kenkey samples. This work demonstrated that the LAB in the ice-kenkey has remarkable inhibitory potential against both Gram-positive and Gram-negative pathogenic strains. In spite of this, producers need to minimise the risk of food-borne diseases through improved food safety and hygienic practices to prevent and inhibit the growth of microbial pathogens during retailing and storage.